Influence of Three Phytase Preparations in Broiler Diets Based on Wheat or Corn: In vitro Measurements of Nutrient Release - Wu, Y.B.; Ravindran, V.; Pierce, J.; Hendriks, W.H. (International Journal of Poultry Science, 2004)
Using an in vitro poultry digestion model, potential beneficial effects from the side activities in a microbial phytase produced by solid state fermentation were examined by comparing the release of phosphorus, reducing sugars and alpha-amino nitrogen by two other phytase preparations in wheat- and corn-based diets. Because of the technology involved, the phytase produced by solid state fermentation is known to contain several side enzyme activities, including protease, amylase, cellulase, xylanase and beta-glucanase. Phytase produced by solid state fermentation released more (P